2019
DOI: 10.1044/2018_ajslp-17-0166
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Comparison of Main Concept Production Between Persons With Aphasia and Persons Without Brain Injury

Abstract: Purpose The purposes of this study are to provide clinicians and researchers with introductory psychometric data for the main concept analysis (MCA), a measure of discourse informativeness, and specifically, to provide descriptive and comparative statistical information about the performance of a large sample of persons not brain injured (PNBIs) and persons with aphasia (PWAs) on AphasiaBank discourse tasks. Method Transcripts of 5 semi-spontaneous disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 54 publications
9
61
0
1
Order By: Relevance
“…Dalton and Richardson showed that these MC checklists were sensitive to differences between PWAs and controls, and reported on other MCA research demonstrating reliability in the scoring and test-retest properties. 22 Hameister and Nickels reported that the PWAs produced fewer MCs than the controls and had greater variability in the order of MCs. 3 The MC checklists and information about MC scoring are available at AphasiaBank's Discourse Analysis link.…”
Section: For Morementioning
confidence: 99%
See 1 more Smart Citation
“…Dalton and Richardson showed that these MC checklists were sensitive to differences between PWAs and controls, and reported on other MCA research demonstrating reliability in the scoring and test-retest properties. 22 Hameister and Nickels reported that the PWAs produced fewer MCs than the controls and had greater variability in the order of MCs. 3 The MC checklists and information about MC scoring are available at AphasiaBank's Discourse Analysis link.…”
Section: For Morementioning
confidence: 99%
“…Special symbols are used to mark a subset of the MCs in each checklist, indicating those that were spoken by 50 and 66% of the respondents. These results have been used for evaluating the performance of large samples of controls (N ¼ 145) and PWAs (N ¼ 238) 22 as well as a small sample (N ¼ 17) of persons with primary progressive aphasia (see Dalton et al in this issue). Using a criterion of 60% or greater, Hameister and Nickels also created a list of MCs for the Cat Rescue task based on 50 control participants from the AphasiaBank database.…”
mentioning
confidence: 99%
“…32 Additionally, a formula for converting codes into scores has been developed by Kong, 56 and modified by Richardson and Dalton. 6 MCA is sensitive to differences between clinical and control populations, 32,[56][57][58][59][60][61] and correlates with listeners' perceptions. 62 Additionally, while different measures have been used (e.g., tau, absolute agreement), all investigations reporting reliability show adequate inter-and intra-rater reliability.…”
Section: Main Concept Analysismentioning
confidence: 99%
“…32 Normative control data, normative PWA data, comparisons between controls and all PWAs, and comparisons of aphasia subtypes to controls have been reported using these checklists. 6,57,64 Although MCA may not have been originally developed with non-transcription based analysis in mind, these tools may allow clinicians to reliably use it in this manner.…”
Section: Main Concept Analysismentioning
confidence: 99%
See 1 more Smart Citation